The performance management playbook : 15 must-have conversations to motivate and manage your people - Bird, Hedda (Pearson, 2021)
"The Performance Management Playbook takes the stress out of managing people. This practical book covers the must-have conversations from daily feedback to annual pay reviews; from dealing with poor performance to setting challenging expectations. With 15 conversation guides to improve your confidence in managing performance, numerous activities to make you and your team less stressed, happier and more productive, as well as toolkits to help you improve performance now, no matter what appraisal process your organisation has in place, this book makes it easy to dip in and develop great performance conversations specific to the challenges you face. Learn from 25 real world examples: from global and local organisations; from 100 employees to over a million; from sectors as varied as financial services, transport, technology, central and local government, TV production, mining,healthcare and construction. The Performance Management Playbook will help you move from anxiety-ridden one-off appraisals to more rewarding regular and meaningful conversations about performance." -- provided by publisher.